The relationship between a numbers of administrative instructions in implementation the process of reducing employees - Agreen Abdoulla Azeez; Tarik Atan (Zanco Journal of Humanity Sciences)
Since 1992, KRG-IRAQ has been established to governing the northern region of Iraq (Kurdistan), with small number of employees and moderate governmental administrations. However, with passing of time this statues changed, especially after 2004, as new central Iraqi government great budget effluent for KRG-IRAQ, that drags with itself recruitment of hundreds thousands of officials. Then, in 2014, political conflicts occurred between central government of Iraq and KRG-Iraq and together with terrorist organization of ISIS war and crude oil price depression makes KRG-IRAQ not be able to pay full monthly employee's salary. This research tries to introduce a guideline for government rightsizing through using of three administrative regulations of; (Reduced work week), Job sharing and Early retirement. A quantitative research methodology has been chose to analyze a specimen of governmental high officers' opinion through questionnaire approach to know how these 3 independent variables effects rightsizing as dependent variable. A questionnaire form created after making case study interview and checking both validity and reliability, three hypotheses were been estimated (H1, H2 and H3). Data analyzed after checking the reliability through frequency and correlation (Bivariate analyses method), the results show high significant correlation of all three administration regulation with the possibility of rightsizing implementation for KRG-Iraq's employees.